NDR kinase Sid2 drives anillin-like Mid1 from the membrane to promote cytokinesis and medial division site placement - Willet, Alaina H. (Curr Biol, 2019)
In animals and fungi, cytokinesis is facilitated by the constriction of an actomyosin contractile ring (CR) [1]. In Schizosaccharomyces pombe, the CR forms mid-cell during mitosis from clusters of proteins at the medial cell cortex called nodes [2]. The anillin-like protein Mid1 localizes to nodes and is required for CR assembly at mid-cell [3]. When CR constriction begins, Mid1 leaves the division site. How Mid1 disassociates and whether this step is important for cytokinetic progression has been unknown. The Septation Initiation Network (SIN), analogous to the Hippo pathway of multicellular organisms, is a signaling cascade that triggers node dispersal, CR assembly and constriction, and septum formation [4,5]. We report that the terminal SIN kinase, Sid2 [6], phosphorylates Mid1 to drive its removal from the cortex at CR constriction onset. A Mid1 mutant that cannot be phosphorylated by Sid2 remains cortical during cytokinesis, over-accumulates in interphase nodes following cell division in a manner dependent on the SAD kinase Cdr2, advances the G2/M transition, precociously recruits other CR components to nodes, pulls Cdr2 aberrantly into the CR, and reduces rates of CR maturation and constriction. When combined with cdr2 mutants that affect node assembly or disassembly, gross defects in division site positioning result. Our findings identify Mid1 as a key Sid2 substrate for SIN-mediated remodeling of the division site for efficient cytokinesis and provide evidence that nodes serve to integrate signals coordinating cell cycle progression and cytokinesis.